An improved FMEA for sustainable risk management in the agri-food industry sector: A mini-review - Wafi'uddin, Izzum; Santoso, Imam; Hidayat, Arif; Lu’ayya, Naila Maulidina; Choirun, Annisa’u (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2024)
Integrating sustainability into risk management is essential for the agri-food sector, as it addresses socio-ecological factors in business operations. Failure Mode and Effect Analysis (FMEA) is widely used for risk management but often lacks precise numerical analysis. This paper subsequently evaluates these enhancements to FMEA, with the objective of (1) conducting a comprehensive examination of research on sustainable risk management in the agri-food industry, and (2) Analyze recent research on improving the FMEA method's effectiveness in risk management. The mini-review is systematically organized by collecting articles, selecting them based on publication year and keywords, screening titles, screening for inclusion, assessing quality through a full-text review, extracting, and analyzing data, and finally reporting the findings. An analysis of 20 papers from 2010 to 2024 was conducted, examining a variety of frameworks. The mini-review was chosen for its flexibility and focus, making it ideal for offering insights with less time and resources. The review results suggest that FMEA has been significantly altered to improve its capabilities, mainly through the integration of fuzzy logic and Data Envelopment Analysis (DEA). Fuzzy FMEA reduces uncertainty, while FMEA-DEA assesses direct and indirect relationships between failure modes, improving risk prioritization. The paper concludes by summarizing the application of FMEA-DEA for sustainable risk management in the agri-food sector.